Pengaruh Self-Efficacy, Komitmen Organisasional, dan Komunikasi Organisasional terhadap Kinerja Pengurus: Studi Pada Anggota KORPS Komunitas Juang PDIP Kabupaten Demak - Euis Soliha; Eko Puji Lestari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this research is to determine and analyze the influence of self-efficacy, organizational commitment, organizational communication on the performance of administrators among members of the PDIP fighting community corps in Demak Regency. This research consists of 3 independent variables, namely self-efficacy, organizational commitment and organizational communication and 1 dependent variable namely management performance. The data collection technique used a questionnare of 45 responden using the method saturated sampling. Using research quantitative. The results of this research can be conclude that : 1. self-efficacy has no effect on management performance 2. organizational commitment has a positive and significant effect on management performance 3. organization communication has a positive and significant effect on management performance.